Traceability of pork - advantages, benefits, monitoring - Petrescu Irina, Elena (Economics of Agriculture, 2010)
Globalization of trade expands distribution of products and services worldwide, making it more difficult to control the content and quality. To prevent "food terrorism it is necessary to know the evolution of animals from birth to end of life. As long as an animal remains in the same group is easily identified by group ID. But once it leaves the farm, things become more complicated and traceability implementation must take into account many factors. For analysis, the firm needs information about vaccination, food, medication and supervision. To prevent consumer illness it is very important to monitor (track) the products chain. If a contaminated batch of food is found it will be easier to identify where they were distributed, and what point in the chain of traceability has been contaminated. Monitoring traceability is a complex process, if we consider the steps taken to obtain meat, and therefore, involves the use of a computer system; making it the classic way is difficult and expensive.